Extramedullary plasmacytoma diagnosed by fine needle aspiration and flow cytometry – case report - Karwicka, Katarzyna; Czabak, Olga; Kozioł, Magdalena; Szudy-Szczyrek, Aneta; Gorący, Aneta; Soroka-Wojtaszko, Maria; Hus, Marek (Journal of Education, Health and Sport, 2019)
The case report presents a patient with multiple myeloma (IgA κ type stage IIIA Durie Salmon stage, with ISS3) diagnosed. The patient had a progressive disease in the direction of extramedullary plasmacytoma. The clinical problem during treatment was a different diagnosis by the histopathology result of tumour. The diagnostic fine needle biopsy was made. The samples were examined using the flow cytometry, which showed the presence of monoclonal plasma cells. The finding of a nodule composed of plasmacytoid cells is possible as a result of the cytometric analysis of outcomes obtained after FNA.